Endogenous Preferences for Parenting and Macroeconomic Outcomes - Nigar Hashimzade (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper investigates the effects of parenting time on macroeconomic outcomes and welfare when parenting choices are determined by own childhood experience and social norms in an overlapping generations framework. Parenting time and material expenditures on children generate children's human capital. When the share of parenting time is relatively low and parenting and leisure are complements or weak substitutes the model has two steady-state equilibria with different welfare levels. In the high-welfare equilibrium parents have stronger endogenous taste for parenting and spend more time with children and less in paid work. Higher productivity due to the higher human capital more than compensates for the reduction in working hours, leading to a higher output level, in comparison to the low-welfare equilibrium.
Keywords: D91; J13; 330; endogenous preferences; parenting; time use; overlapping generations; human capital